ANALISIS KETERKAITAN KETERSEDIAAN INFRASTRUKTUR DENGAN PERTUMBUHAN EKONOMI DI INDONESIA: PENDEKATAN ANALISIS GRANGER CAUSALITY - Sembanyang, Lesta Karolina B (JEJAK: Jurnal Ekonomi dan Kebijakan, 2011)
The aims of this study are to analyze the causal relationship of public service provision (infrastructure), economic growth and tax inIndonesiaand to formulate the policy implications of causal link and infrastructure inIndonesiaâs economic growth. The data used was time series data, from 1987 up to 2009. They were from many sources such as Government Expenditure (APBN), Central Bureau of Statistics (BPS) and the International Financial Statistics (IFS). The method used is a causal analysis approach or the Granger causality. The findings of this study is that there is a direct relationship between GDP to infrastructure and the GDP to tax revenue. The conclusions of this study are Gross Domestic Product (GDP) can lead the availability of infrastructure (for example road length) in Indonesia,there is a causal connection between the economic growth and the tax revenue in Indonesia, andthe increased tax revenue will increase the availability of infrastructure, especially road.